Table of Content - - (Journal of medical and pharmaceutical sciences, 2025)
Table of Content:• The Role of Patient Complaint Handling in Improving Healthcare Quality: A Field Study at Jazan General Hospital - Kingdom of Saudi Arabia 2025Dr. Hamad Mohammed Mania, Mrs. Mona Ali Daraaj• Epidemiological Analysis of Diphtheria Cases in Hodeida, Yemen:  A Review of Admission Records from 2018 to 2022Dr. Najeeb M.S. Moulhee, Dr. Sadeq Abdo Mohammed Alwesabi  ,Dr. Mogeeb Saeed Taha , Dr. Ahmed Suliman Mohamed Majam• Comparative Study of Psoriasis and Atopic DermatitisAsst- Lecturer / Fatima Rashid Mohan• Ultrasound-Detected Metabolic Dysfunction-Associated Steatotic Hepatopathy (MASH) Prevalence in Type 2 Diabetes Patients Attending Primary CareMuammar Basheer Yasir,  Dr. Al-Mottesembellah Abdalruhman Gaiz, Noor Abdulredha Jaleel• Cancer Burden in the Red Sea State, Sudan: A Ten Years of Incidence, Distribution, and Trends: (2016 - June 2025)Dr. Awad Abdalla Widaa
Keywords: Journal of Medical and Pharmaceutical Sciences